THE INFLUENCE OF GOOD CORPORATE GOVERNANCE AND AUDIT QUALITY AGAINST THE DISCLOSURE OF CORPORATE SOCIAL RESPONSIBILITY - Darwin Marasi Purba (The Accounting Journal of Binaniaga, 2016)
This study aimed to get empirical evidence about the influence of good corporate governance consists of the proportion of institution ownership, board size, the proportion of independent commisioners, audit committee size and audit quality on the disclosure of corporate social responsibility with leverage as control variables.Population of this research are manufacturing companies listed in Indonesia Stock Exchange in 2014 the annual report contains disclosure of corporate social responsibility activities of companies which some 59 companies using purposive sampling technique. Methods of data analysis using descriptive statistical analysis and multiple linear regression.These results indicate that good corporate governance and audit quality has a significant effect simultaneously on the disclosure of corporate social responsibility of the company. However, partial test results showed that the proportion of institutional ownership, board size, the size of the audit committee and audit quality is not affected by the disclosure of corporate social responsibility. While the proportion of independent commisioners have a negative significant effect on the disclosure of corporate social responsibility.Keyword: good corporate governance, corporate social responsibility disclosure.